2019
DOI: 10.7759/cureus.4470
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol in the Treatment of Castration-resistant Prostate Cancer: A Lower-middle-income Country Experience

Abstract: Introduction: Prostate cancer is the second most common cancer and the fifth leading cause of death worldwide. Its metastatic stage is associated with considerable morbidity and may lead to death. In Pakistan, given the high levels of economic constraint, patients with castration-resistant metastatic prostate cancer can be treated with cost-effective medications like diethylstilbestrol (DES). Objectives: The goal of this study was to assess the efficacy and adverse effects of DES when used in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This study has limitations associated to its retrospective nature. However, as future directions, low-dose DES, starting from a 1 mg dose, could be studied in prospective randomized studies in comparison to already available later-line treatments, with the intention of finding active therapies that are cost effective for patients and health-care systems, particularly in resource-limited settings such as Mexico and many other LMICs 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This study has limitations associated to its retrospective nature. However, as future directions, low-dose DES, starting from a 1 mg dose, could be studied in prospective randomized studies in comparison to already available later-line treatments, with the intention of finding active therapies that are cost effective for patients and health-care systems, particularly in resource-limited settings such as Mexico and many other LMICs 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to targeting AR activity, it has long been known that estrogens are highly effective at treating advanced PCa [ 11 ]. Despite associated cardiovascular toxicity initially limiting their clinical use [ 11 , 12 ], both estrogen [ 13 , 14 ] and diethylstilbestrol [ 15 , 16 ] have recently been re-investigated in PCa treatment. The tumor suppressive effects of estrogens were originally thought to be facilitated by estrogen receptors ERα and ERβ, but recent research from our lab has identified a third ER, G-protein Estrogen Receptor 1 (GPER1), that plays a critical role in suppressing PCa growth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DES was used until 1985, when it was replaced by leuprolide to treat advanced prostate cancer. However, DES is still used in lower and middle-income countries as a treatment for castration-resistant prostate cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%